An Investigation for the Spin Hamiltonian sParameters and the Local Structure for Co2+ in ZnWO4 - Ding Chang-Chun; Wu Shao-Yi; Xu Yong-Qiang; Zhang Li-Juan (MATEC Web of Conferences, 2016)
Based on the perturbation formulae of the spin Hamiltonian parameters (SHPs), i,e,. g factors gx, gy, gz, and hyperfine structure constants Ax, Ay, Az, for a 3d7 ion in rhombically distorted octahedra, the defect structure and the experimental EPR spectra are theoretically investigated for the rhombic Co2+ centre in ZnWO4. Due to the Jahn-Teller effect, the impurity ion Co2+ on host Zn2+ site is found to undergo the local rhombic elongation distortion, characterized by the axial elongation ΔZ (≈ 0.157 Å) of the impurity-ligand bonds and the perpendicular distortion angle Δф (≈ 3.5°) related to an ideal octahedron. Compared with host Zn2+ site in ZnWO4, the Co2+ centre exhibits a more regular oxygen octahedron. All the calculated SHPs show good agreement with the observed values. The present work may be helpful to understand the local structures and properties of metal tungstate with transition-metal dopants.